Clinical research reactivation during the COVID-19 pandemic: An academic center process and lessons for the future. Issue 1 (2022) - Armstrong, Jennifer; Lakin, Alison; Blumberg-Romero, Laurie; Campbell, Thomas; Heldens, John; Lieu, Christopher; Sandene, Jenae Neiman. Erin; Steinbeiss, Matthew; Thompson, Darcy; Tregellas, Jason; Flaig, Thomas; Higgins, Janine
No abstract available